2021
DOI: 10.1111/1753-0407.13206
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body mass index, glycosylated hemoglobin A1C, blood pressure, and LDL‐cholesterol among type 2 diabetes patients in Malaysia: A population‐based longitudinal study

Abstract: Background This study aimed to describe changes in body mass index, glycosylated hemoglobin A1C, blood pressure, and low‐density lipoprotein (LDL)‐cholesterol among type 2 diabetes patients in Malaysia. Methods A five‐year retrospective cohort study was conducted using data from the National Diabetes Registry. Type 2 diabetes patients aged ≥18 years and had ≥2 clinical audits between 2013 and 2017 were included in the analysis. The first audit information formed the baseline characteristics, and the last audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Our study findings can be externally generalized to the Malaysian population because of similar demographic characteristics, as previously reported ( Ministry of Health Malaysia, 2013 ; Wan et al, 2021a ; Wan et al, 2021b ). A previous study found that the mean LDL-C decreased from 3.2 mmol/L in 2009 to 3.1 mmol/L in 2012 ( Ministry of Health Malaysia, 2013 ).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our study findings can be externally generalized to the Malaysian population because of similar demographic characteristics, as previously reported ( Ministry of Health Malaysia, 2013 ; Wan et al, 2021a ; Wan et al, 2021b ). A previous study found that the mean LDL-C decreased from 3.2 mmol/L in 2009 to 3.1 mmol/L in 2012 ( Ministry of Health Malaysia, 2013 ).…”
Section: Discussionsupporting
confidence: 80%
“…This was a retrospective open cohort study of T2D patients receiving diabetes care from public primary care clinics in Negeri Sembilan state, Malaysia, the details of which had been reported previously ( Wan et al, 2021a ; Wan et al, 2021b ). This population-based open cohort dataset was sourced from Malaysia’s National Diabetes Registry, and adult T2D patients with at least two diabetes clinical audits between 2013 to 2017 were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite there being no comprehensive consensus on clinical significance of glycemic variability, studies showed that FPG variability is associated with increased risk of adverse events and specific diseases, including cardiovascular events, peripheral neuropathy, retinopathy, and arterial stiffness ( 9 13 ). Clinical practice and research have focused on HbA1c in T2DM patients, rather than the potential role of HbA1c variability ( 14 16 ). Our results suggest that higher HbA1c variability increases the incidence of severe hypoglycemia, indicating that it is important to carefully observe in T2DM patients with higher HbA1c variability and take precautions, even when acceptable levels of HbA1c and FPG are achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of DKD among type 2 diabetes (T2D) patients in the country was reported to be only 14.6% in 2019 11 . As the reported prevalence was relatively lower than that reported elsewhere across the globe 1 , 5 , underreporting of the condition and under-screening for DKD were postulated as potential explanations 11 , 12 . For perspective, the prevalence of CKD among the general adult population in Malaysia was 15.5% in 2018 13 .…”
Section: Introductionmentioning
confidence: 91%